Optimizing Inclusive Education: Uncovering Challenges and Strategies in Primary Schools Through a Literature Review - Ediyanto, Ediyanto; Mahanani, Putri; Aprilia, Imas Diana; Ramadhani, Risa Safira; Wulandary, Verra (Mimbar Sekolah Dasar, 2024)
Inclusive education means that every student, including those with special needs, has the right to an education in an inclusive school environment. In the context of inclusive education, several fundamental obstacles stand in the way of creating an inclusive and supportive learning environment. The current study aims to provide a deeper understanding of the importance of inclusive education and the steps that can be taken to ensure that every child, including those with special needs, can benefit from a balanced and equitable education. The method used in writing this article is a literature review, with the ten articles used being literature published in 2020-2023 Articles were selected by determining the scope, selecting relevant keywords, and writing eligible articles related to the implementation of inclusive education in Indonesia. The results show that most schools in Indonesia have an understanding of inclusive education but still need to improve their implementation. Factors include the need for more special assistant teachers, socialization of inclusion policies, and limited budgets. Although some schools have implemented the inclusion program well, there are still challenges, including a need for more understanding from the community and parents, a shortage of human resources, and barriers to the optimality of inclusive education activities. In implementing inclusive education, success factors involve teachers' attitudes and knowledge, communication, and adequate infrastructure.